Clinical Utility of Procalcitonin in the Diagnosis of Pneumonia. (4th February 2020) - Wussler, Desiree; Kozhuharov, Nikola; Tavares Oliveira, Mucio; Bossa, Aline; Sabti, Zaid; Nowak, Albina; Murray, Karsten; du Fay de Lavallaz, Jeanne; Badertscher, Patrick; Twerenbold, Raphael; Shrestha, Samyut; Flores, Dayana; et al.
Abstract: BACKGROUND: The clinical utility of procalcitonin in the diagnosis and management of pneumonia remains controversial. METHODS: We assessed the clinical utility of procalcitonin in 2 prospective studies: first, a multicenter diagnostic study in patients presenting to the emergency department with acute dyspnea to directly compare the diagnostic accuracy of procalcitonin with that of interleukin 6 and C-reactive protein (CRP) in the diagnosis of pneumonia; second, a randomized management study of procalcitonin guidance in patients with acute heart failure and suspected pneumonia. Diagnostic accuracy for pneumonia as centrally adjudicated by 2 independent experts was quantified with the area under the ROC curve (AUC). RESULTS: Among 690 patients in the diagnostic study, 178 (25.8%) had an adjudicated final diagnosis of pneumonia. Procalcitonin, interleukin 6, and CRP were significantly higher in patients with pneumonia than in those without. When compared to procalcitonin (AUC = 0.75; 95% CI, 0.71–0.78), interleukin 6 (AUC = 0.80; 95% CI, 0.77–0.83) and CRP (AUC = 0.82; 95% CI, 0.79–0.85) had significantly higher diagnostic accuracy ( P = 0.010 and P < 0.001, respectively). The management study was stopped early owing to the unexpectedly low AUC of procalcitonin in the diagnostic study. Among 45 randomized patients, the number of days on antibiotic therapy and the length of hospital stay were similar (both P = 0.39) in patients randomized to the procalcitonin-guided group (n = 25) and usual-care group (n = 20). CONCLUSIONS: In patients presenting with dyspnea, diagnostic accuracy of procalcitonin for pneumonia is only moderate and lower than that of interleukin 6 and CRP. The clinical utility of procalcitonin was lower than expected. SUMMARY: Pneumonia has diverse and often unspecific symptoms. As the role of biomarkers in the diagnosis of pneumonia remains controversial, it is often difficult to distinguish pneumonia from other illnesses causing shortness of breath. The current study prospectively enrolled unselected patients presenting with acute dyspnea and directly compared the diagnostic accuracy of procalcitonin, interleukin 6, and CRP for the diagnosis of pneumonia. In this setting, diagnostic accuracy of procalcitonin for pneumonia was lower as compared to interleukin 6 and CRP. The clinical utility of procalcitonin was lower than expected. ClinicalTrials.gov Identifier: NCT01831115.